THE USE OF CLASSICAL RAGA YEMEN IN CINE MUSIC - AN IDEA: सिने संगीत में शास्त्रीय राग यमन का प्रय¨ग - एक विचार - Sahastrabuddhe, Bhagyashree (International Journal of Research -GRANTHAALAYAH, 2015)
Hindustani music is based on raga. The definition of raga has been given by different scholars with their own method, but the meaning of all has been referenced by "sound" in particular, the voice of the Varna Varnishtha: Ranjjjan, Chittananas: Raga: The so-called "Buddha". Therefore, it can be said that the soul of Indian music resides only in the raga composition which creates the pigmentation with the tone and color. The railing structure stands on the building box. On the rough side, it is assumed that in the construction of an octave, the original 12 vowels are the same in the construction of the rhyme, in preparing the structure of a building. The foundation work is done. हिन्दुस्तानी संगीत राग पर आधारित है। राग की परिभाषा अलग-अलग विद्वान¨ं ने अपनी-अपनी पद्धति से दी है परन्तु सबका आशय ”य¨ऽयं ध्वनिविषेषस्तु स्वर वर्ण विभूषितः रंजक¨जन चित्तानां सः रागः कथित¨ बुेधैः“ से ही संदर्भित रहा है। अतः यह कहा जा सकता है कि भारतीय संगीत की आत्मा स्वर, वर्ण से युक्त रंजकता पैैदा करने वाली राग रचना में ही बसती है। स्वर¨ं क¢ बिल्ंिडग बाॅक्स पर राग का ढाँचा खड़ा ह¨ता है। मोटे त©र पर ये माना गया है कि एक सप्तक क¢ मूल 12 स्वर सा रे रे ग ग म म प ध ध नि नि राग क¢ निर्माण में वही काम करते हैं ज¨ किसी बिल्डिंग क¢ ढाँचे क¨ तैयार करने में नींव का कार्य ह¨ता है।